2022
DOI: 10.1111/twec.13365
|View full text |Cite
|
Sign up to set email alerts
|

Regional integration and non‐tariff barriers to Intra‐Sub‐Saharan Africa trade

Abstract: The paper assesses the ex‐post trade effect of sub‐regional trade agreements (RTAs), financial integration and other non‐tariff barriers on intra‐regional trade involving 43 Sub‐Saharan Africa (SSA) countries. The objective is to find out if RTAs within SSA had increased trade flows to inform current efforts of establishing a successful continental free trade area in SSA. Estimating a gravity model augmented with measures of trade agreements and financial integration, the paper made use of bilateral trade flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The significant struggles in sub-Saharan Africa have all contributed to a higher mortality rate in traumatic chest injuries [ 18 , 29 ]. This implies that the mortality of patients following chest injury in sub-Saharan Africa is considerably greater than in high income countries, with no change in trends from 2012 to 2015 [ 51 , 52 ]. This underscores the need for action-based interventions focused on health system improvement and a trauma reduction plan.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The significant struggles in sub-Saharan Africa have all contributed to a higher mortality rate in traumatic chest injuries [ 18 , 29 ]. This implies that the mortality of patients following chest injury in sub-Saharan Africa is considerably greater than in high income countries, with no change in trends from 2012 to 2015 [ 51 , 52 ]. This underscores the need for action-based interventions focused on health system improvement and a trauma reduction plan.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prevalence of road traffic accidents (RTA) in sub-Saharan Africa (SSA) is a major challenge, contributing significantly to chest trauma [ 52 ]. For example, recent studies in Ethiopia and Tanzania revealed that RTAs accounted for 44.5% and 50.7%, respectively, with mortality following chest trauma reaching 27.6% [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Turkson et al [11] find sub-regional trade agreements within Sub-Saharan Africa and especially among Economic Community of West African States and Southern Africa Development Community members to have had a positive and significant impact on bilateral trade. Financially integrated trading partners also traded more, while we also found distance, landlockedness, common currency and colonial link to have an impact on trade costs and bilateral trade flows within SSA.…”
Section: Review Of Literaturementioning
confidence: 99%